“Sulla soglia”. La spazialità delle relazioni nelle istituzioni prescolastiche durante la pandemia di Covid-19 - Tassan, Manuela (Antropologia Pubblica, 2024)
Based on research conducted with teachers from municipal infant-toddler centers (0-3 years) and preschools (3-6 years) in Milan and Reggio Emilia (Italy), this article examines the changes in educational practices brought about by the Covid-19 pandemic, with a particular emphasis on people’s relationship with school spaces and places. The article demonstrates how the measures implemented to contain the virus, such as creating “bubbles”, enforcing physical distancing, and limiting the use of objects, have highlighted the essential role of “spatiality of relationships” within educational services. By “spatiality of relations”, I mean those relationships that are shaped by and cannot be fully understood without considering the specific spaces, also with their architectural peculiarity, in which they occur. On the one hand, the text explores the feeling of having to remain “on the threshold”, as teachers said, in a literal and metaphorical sense, since teachers and children could not fully experience the spaces and places of the school and could not build or deepen the usual relationships with teachers and children from other classes due to health restrictions. On the other hand, the article also analyzes their resilient agency in redefining relationships with places precisely through movement in space, which became essential with the obligation not to create assemblages. These processes of resemantizing places made it possible to keep alive inter- and intra-generational relationships, continuing to build a sense of identity belonging to infant-toddler centers and preschools even in a critical period of suspension of the usual forms of sociability.